An accretion disc-irradiation hybrid model for the optical/UV variability in radio-quiet quasars. (29th June 2016) - Liu, Hui; Li, Shuang-Liang; Gu, Minfeng; Guo, Hengxiao
Abstract : The optical/ultraviolet (UV) variability of quasars has been discovered to be correlated with other quasar properties, such as luminosity, black hole mass and rest-frame wavelength. However, the origin of variability has been a puzzle so far. In this work, we upgrade the accretion disc model, which assumed the variability is caused by the change of global mass accretion rate, by constraining the disc size to match the viscous time-scale of accretion disc to the variability time-scale observed and by including the irradiation/X-ray reprocessing to make the emitted spectrum become steeper. We find this hybrid model can reproduce the observed bluer-when-brighter trend quite well, which is used to validate the theoretical model by several works recently. The traditional correlation between the variability amplitude and rest-frame wavelength can also be well fitted by our model. In addition, a weak positive correlation between variability amplitude and black hole mass is present, qualitatively consistent with recent observations.